Self-Control Demand Affects Procrastination: Moderated by Proactive Behavior and Perceived Social Support From Educators and Lecturers in Higher Education Institutions - Alif, Muhammad Ikhsan; Fitria, Irma; Handayani, Selvian; Hidayat, Muhammad Afdelpiero; Syabina, Masayu Sitti Nur (International Journal of Educational Management and Innovation, 2025)
Background. This study aims to examine: (1) the impact of self-control demands on procrastination, (2) the moderating role of proactive behavior in weakening the positive relationship between self-control demands and procrastination, and (3) the moderating effect of perceived social support on the influence of self-control demands on procrastination. The research subjects consisted of the academic community, specifically educators and lecturers in higher education institutions. Methods. Primary data were collected using a purposive sampling method, involving 190 respondents, and analyzed using the Partial Least Squares (PLS) approach within Structural Equation Modeling (SEM) with the Warp-PLS 8.0 software. Results. The findings reveal that, contrary to some theoretical expectations, higher self-control demands are significantly associated with lower levels of procrastination. Furthermore, the analysis uncovers significant and complex moderation effects. A unique and counterintuitive finding emerged regarding proactive behavior, which positively moderated the relationship. This indicates that for highly proactive individuals, the pressure of high self-control demands is linked to increased procrastination, potentially because their high personal standards and initiative lead to greater psychological resource depletion. Perceived social support also demonstrated a significant, though similarly complex, positive moderating effect, suggesting that it may weaken the beneficial impact of self-control. Conclusion. These findings yield critical practical implications. Rather than simply encouraging proactivity, higher education institutions must provide resources to manage the associated psychological strain. It is recommended that institutions implement structured, task-oriented support systems, such as formal mentorship, and design workload management policies that prevent excessive self-control demands, thereby preserving educator well-being and reducing procrastination.